The International and Political Journal: Political – socialization : A study in the foundations and future dimensions . - Ibrahim , Prof.Dr Nadhim nawaf (The International and Political Journal, 2024)
The individual as organic object from and becomes a social organic being through society and its prevailing culture . hence the individual is born and grows in the society according to a given culture system that learned by the individuals through their, knowledge of the values and behavior , trends and roles which expected from them to achieve the demands of the individual from ,the society and the demands of society from the individual and this comes through the role of political-socialization and its political institutions responsible for it and this requires the following : preparing a citizen with positive qualities and a believer in freedom of opinion and respect for each of the . deployment and consolidation of tolerance and multicultural values . learning positive attitudes and values . developing education curricula positivity . establishing media and partisan institutions and civilized targeted civil society organizations.